Spatiotemporal Variation of Osmanthus fragrans Phenology in China in Response to Climate Change From 1973 to 1996 - Wang, Xianping; Liu, Yinzhan; Li, Xin; He, Shibin; Zhong, Mingxing; Shang, Fude (Frontiers in Plant Science, 2022)
Climate change greatly affects spring and autumn plant phenology around the world, which means that climate change also significantly impacts ecosystem function and the social economy. However, there is still much to be learned about autumn plant phenology, especially about autumn flowering phenology. In this study, we examined the spatiotemporal pattern of Osmanthus fragrans phenology. This includes both leaf phenology (the dates of bud-bust, BBD; first leaf unfolding, FLD; 50% of leaf unfolding, 50 LD) and flowering phenology (the dates of first flowering, FFD; peace of flowering, PFD; end of flowering, EFD). Stepwise multiple linear regressions were employed to analyze the relationships between phenophases and climatic factors in the long term phenological data collected by the Chinese Phenological Observation Network from 1973-1996. The results showed that spring leaf phenophases and autumn flowering phenophases were strongly affected by latitude. BBD, FLD and 50LD of O. fragran were increasingly delayed by 3.98, 3.93 and 4.40 days as per degree of latitude increased, while FFD, PFD and EFD in O. fragrans increasingly advanced 3.11, 3.26 and 2.99 days, respectively. BBD was significantly delayed during the entire study period and across the region, but no significant trends were observed in either FLD or 50LD. All flowering phenophases of O. fragrans were delayed. Both leaf and flowering phenophases correlated negatively with growing degree-days (GDD) and cold degree-days (CDD) (P < 0.001), respectively. BBD and FLD were negatively correlated with total annual precipitation (P < 0.01). In addition to the effects of climate on autumn flowering phenology, we found that earlier spring leaf phenophases led to delayed autumn flowering phenophases (P < 0.001). Our results suggest that future climate warming might further delay the phenological sequence of autumn flowering species O. fragrans, and this may be true for other autumn flowering plants as well.